Induced maturation and spawning of banana prawn, Penaeus merguiensis de Man, under captivity in the inshore waters of Karwar - Zacharia, Sherly; Kakati, V S (Indian Journal of Fisheries, 2011)
Investigations were made on the ovarian maturation of banana prawn (Penaeusmerguiensis) held in a fixed hapa (2xlxlm) in inshore waters of Karwar bay. Theshrimps collected (ablated females and males in the ratio 2:1) were subjected toexperimental condition for a period of 10 days. The parameters such as salinity,temperature, pH and primary productivity of the seawater at the site were monitoredregularly. Within 3-6 days after eyestalk ablation, 70% of the femalesmatured in the cage and spawned successfully in situ, thereby indicating thepossibility of induced ovarian maturation on commercial scale. Brood stock developmenton commercial scale for other important candidate species of aquaculturehas been suggested.